2012
DOI: 10.5001/omj.2012.121
|View full text |Cite
|
Sign up to set email alerts
|

Patient’s Knowledge and Perception Towards the use of Non-steroidal Anti-Inflammatory Drugs in Rheumatology Clinic Northern Malaysia

Abstract: This study shows that half of the patients who attended the rheumatology clinic were unaware of the side effect of NSAIDs. Available data showed that most of the knowledgeable patients are more conscience and self-educated. This study also reveals the important roles of clinicians, trained staff nurses as well as the pharmacist in providing the guidance and knowledge of any medication taken by patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Furthermore, almost half of respondents got information on side effects by reading drug literature inserted in the packs while few got it from TV (15.2%) and radio broadcast (7.4%). This is similar to the findings of Wahinuddin et al who also reported that 15% obtained information by surfing the internet and 9.2% from printed media in rheumatology clinic at Northern Malaysia [34]. Diclofenac (voltaren retard) was the most frequently prescribed NSAID followed by ibuprofen (ibrucap) and this is consistent with the findings of Albsoul-Younes et al in a Jordanian population [40].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, almost half of respondents got information on side effects by reading drug literature inserted in the packs while few got it from TV (15.2%) and radio broadcast (7.4%). This is similar to the findings of Wahinuddin et al who also reported that 15% obtained information by surfing the internet and 9.2% from printed media in rheumatology clinic at Northern Malaysia [34]. Diclofenac (voltaren retard) was the most frequently prescribed NSAID followed by ibuprofen (ibrucap) and this is consistent with the findings of Albsoul-Younes et al in a Jordanian population [40].…”
Section: Discussionsupporting
confidence: 91%
“…This might be attributed to the tertiary educational and post graduate qualifications of most respondents. Wahinuddin et al reported that factors such as knowledge, attitudes and motivation are important for patient compliance; and the effectiveness of therapy and that these factors might be influenced by the patient's education level, gender, the type of the disease and medication, as well as doctor-patient relationship, and culture [34]. The majority of participants (73%) were placed on NSAIDs by medical practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…The topic of patients’ knowledge about adverse health effects of NSAIDs has also been studied by the international scientific community. A study among 120 patients attending the rheumatology clinic in a hospital in Malaysia and using NSAIDs for at least three months, reported that more than half of the participants were aware of various side effects of NSAIDs, with significantly more females than males being aware of such adverse effects ( 8 ). Also, low socioeconomic status and educational level were associated with lower proportions of patients aware of side effects of NSAIDs ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…A response rate of 50% and 95% confidence interval was assumed. 6 A sample size of 377 individuals was determined. Participants' in the age group of 18-65 years were included in this study.…”
Section: Methodsmentioning
confidence: 99%